How law developed by different judicial system - a comparison study between the English and Malaysian legal system with particular reference on defense of provocation / Hanizah Asmooni … [et al.] - Asmooni, Hanizah; Md Shariff, Nurshela; Majid, Nur Fazrah; Wahed, Wan Nur Ilani (2009)
Law could be developed via many ways and means. One of the ways is through decisions made by courts. This applied in both criminal and civil cases. In murder cases, there are various defences available for the accused in order to escape the death penalty. One of the defences open for the accused is that whilst doing the act (killing), he was deprived of his self control due to provocation received by him from the deceased. Provocation is recognised under the common law system (United Kingdom) whereby if it successfully pleaded, the crime of murder will be mitigated to manslaughter and the death penalty will be replaced with a lesser punishment which usually will be imprisonment for a period that shall be determined at the discretion of the court. In Malaysia, the defence of provocation was encoded as an exception to murder. The work ability of this defence is similar to the common law whereby if an accused succeeded in pleading this defence, he will be guilty for culpable homicide not amounting to murder and shall be punished with imprisonment. Though provocation is recognised in United Kingdom and Malaysia, but the way the merits and evidence brought by the accused differs in both countries whereby in United Kingdom, the sitting judge shall determine on question of law and the jury shall decide on question of fact and pass their verdict. In Malaysia, the sitting judge shall be the sole determiner on both question of law and fact. This different judicial system had contributed in the development of the law on provocation. It is hoped that this research shall give a clear view on the development of such law by the different judicial system.